Share
Explore BrainMass

Solve the system of equations by Elimination Method

Solve each system by the elimination method. Check each solution. See Examples 1 and 2.

1. x + y = 2 3. 2x + y = -5 5. 3x + 2y = 0
2x - y = -5 x - y = 2 -3x - y = 3

2. 3x - y = -12 4. 2x + y = -15 6 . 5x - y = 5
x + y = 4 -x - y = 10 -5x + 2y = 0

Example 1 - Using the Elimination Method
Use the elimination method to solve the system.
x + y = 5
x - y = 3
Each equation in this system is a statement of equality, so the sum of the
left sides equals the sum of the right sides. Adding in this way gives
(x + y) + (x - y) = 5 + 3.

Combine like terms and simplify to get
2x = 8
x = 4 . Divide by 2.
Notice that y has been eliminated. The result, gives the x-value of the
solution of the given system. To find the y-value of the solution, substitute 4
for x in either of the two equations of the system.

Check the solution set found at the side, {(4, 1)}, by substituting 4 for x and
1 for y in both equations of the given system.
Check -
x + y = 5
4 + 1 _ 5
5 = 5 true

x - y = 3
4 - 1 _ 3
3 = 3 true
Since both results are true, the solution set of the system is {(4, 1)}.

Example 2
Solve the system.
y + 11 = 2x
5x = y + 26

Step 1 Rewrite both equations in the form to get the system
-2x + y = -11 Subtract 2x and 11.
5x - y = 26. Subtract y.

Step 2 Because the coefficients of y are 1 and adding will eliminate y.
It is not necessary to multiply either equation by a number.
Step 3 Add the two equations. This time we use vertical addition.

-2x _ y = -11
5x _ y = 26
3x = 15 Add in columns

Step 4 Solve the equation.
3x = 15
X = 5 divide by 3.

Step 5 Find the value of y by substituting 5 for x in either of the original
equations. Choosing the first equation gives
y + 11 = 2x
y + 11 = 2 (5) let x = 5.
y + 11 = 10
y = _1. Subtract 11.

Please see attached file.

Attachments

Solution Summary

The solution provides step by step method to solve the system of equations by elimination method. The solution also check the roots by substitution.

$2.19